ANALISIS DESKRIPTIF TERKAIT PENGETAHUAN PENGGUNAAN ANTIBIOTIK PADA WARGA RW 009 KELURAHAN DUREN SAWIT PERIODE MEI-JUNI 2022 - Fidia, Fachdiana; Tuahuns, Farida; Niode, Harum Andini Putri (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Infectious diseases remain one of the world's public health concerns, particularly in developing countries. Excessive and inappropriate antibiotics use can lead to the emergence of bacterial resistance and increase the economic burden of health care; additionally. According to a preliminary survey conducted on residents of 009 Community Unit, Duren Sawit Sub-district aged 17-65 in January 2022, it demonstrated that 60% residents believed that antibiotics could treat fever and could be purchased without a prescription 40%. This research aimed to describe the knowledge of antibiotic use in the residents of 009 Community Unit, Duren Sawit Village. The study employed a descriptive quantitative type, where data collection was performed using a questionnaire. This research comprised 237 respondents, who were selected employing the proportional random sampling technique and required the inclusion criteria. The study’s findings indicated that out of 237 respondents, 99 individuals (42%) had good comprehension, 88 individuals (37%) had sufficient comprehension, and 50 individuals (21%) had inadequate comprehension. In summary, suppose described in each indicator, the level of public knowledge for the three indicators was as follows: 118 respondents (50%) have a good understanding of the meaning of antibiotics,104 respondents (44%) have a good understanding of the use of antibiotics, and 140 respondents (59%) had a good understanding of the undesirable effects of the use of antibiotics. The 4 most consumed antibiotics were Amoxicillin (55.7%), Fg Troches (14.3%), Cefixime (8.4%) and Azithromycin (8.4%). While the dose of taking antibiotics ranges from 1x to 4x a day, depends on the type of antibiotics.